Exploring inconsistencies in environmental impact assessments of organic farming - Hikaru Komatsu; Jeremy Rappleye (Academia Environmental Sciences and Sustainability)
Despite the growing popularity of organic farming, persistent questions surround its environmental effects. A 2017 meta-analysis suggested elevated acidification and eutrophication potentials per unit of agricultural production for organic farming relative to conventional farming. However, a recent 2023 meta-analysis contradicted these findings. This brief communication article reveals that the disparities between these meta-analyses stem from differences in averaging methods and sample sizes. The 2023 meta-analysis, employing a more robust averaging method and a larger sample size, suggests that researchers should incorporate the 2023 findings into their investigations, potentially necessitating a reconsideration of agricultural policies and dietary choices to align with updated environmental impact assessments.